Implementing HSSE Through a Safety Culture Perspective to Enhance Maritime Safety Performance: A Study on Medium-Sized Vessels in Indonesia - Riki Wanda Putra; Perengki Susanto; Rosyeni Rasyid; Hasri Devin; Nasra Noviandani (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
This study examines how the implementation of Health, Safety, Security, and Environment (HSSE) practices is associated with the shaping of safety behavior and perceived maritime safety performance on medium-sized vessels in Indonesia. Adopting an interpretivist qualitative approach, the study employs a single-case study design with data collected through semi-structured interviews with 18 crew members across managerial, operational, and support levels, complemented by field observations and archival safety documents. Guided by the Gioia methodology, the analysis identifies three interrelated mechanisms through which HSSE practices are interpreted and enacted at the shipboard level: the internalization of safety values through leadership and safety communication, the reinforcement of safe behavior through collective norms and peer accountability, and the enactment of trust-based reporting and continuous learning. The findings suggest that HSSE does not automatically translate into high safety performance; rather, its effectiveness is understood to be contingent upon the presence of a supportive safety culture and the enactment of everyday safety behaviors by crew members. Supportive safety leadership, two-way communication, and non-punitive reporting systems are consistently described as facilitating safety compliance and safety participation, which are associated with heightened risk awareness, improved coordination across shipboard functions, and fewer unsafe acts during complex operations. Theoretically, this study advances HSSE and safety culture scholarship by explicitly conceptualizing safety culture as a social and interpretive mechanism that mediates the translation of formal HSSE systems into lived safety practices. By moving beyond a procedural view of HSSE, the study extends Safety Culture Theory through a micro-operational perspective, offering analytically transferable insights for similar high-risk maritime contexts.